Los factores sociales y el consumo de sustancias psicoactivas en los adolescentes de la Unidad Educativa Municipal del cantón Quevedo - Villavicencio Duque, Yimpol (2017)
This research aims to promote intraspecific prevention, avoiding the use of drugs among young people, since it is considered necessary that parents have an effective communication with children to feel mentally and emotionally stable and safe, because they have no reason to go to the substance that destroy their lives The theoretical framework is based on the inductive and analytical method, this method breaks down the whole, examines each part and draws conclusions. The types of research that have been applied are of the following types: descriptive, explanatory and participatory; the sample was not robotic, considering that the population is small. The techniques used in this study are: observation, interview and questionnaire, the same ones that helped in the development of the research. The foundations that were used were sociological, because the topic is social, psychological, pedagogical and, in particular, the technological base, which is the basis for proposing this topic. The realization of a series of tests allowed to know the level of knowledge that the layers have on the subject, which is very low, and this allowed to justify the conclusion: development and preparation of printed materials for prevention and guidance.